1998
DOI: 10.1124/mol.54.3.504
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status Modulates Rat Liver Cytochrome P450 Arachidonic Acid Metabolism

Abstract: Alterations in nutritional status affect hepatic cytochrome P450 levels. Since cytochromes P450 participate in the metabolism of arachidonic acid, we hypothesized that changes in liver P450 arachidonic acid metabolism occur during fasting and refeeding. Male Fisher 344 rats were either fed, fasted 48 hr (F48), fasted 48 hr and then refed 6 hr (F48/R6), or fasted 48 hr and then refed 24 hr (F48/R24). F48 rats had reduced body weight, increased plasma ␤-hydroxybutyrate, and reduced plasma insulin compared with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 35 publications
(70 reference statements)
1
15
0
Order By: Relevance
“…After transfection with CYP2C11, there was a 9% increase in 14,15-EET and a 46% increase in 11,12-EET. These data are consistent with the known regiochemical selectivity of CYP2C11 (Qu et al, 1998) Fig. 5.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…After transfection with CYP2C11, there was a 9% increase in 14,15-EET and a 46% increase in 11,12-EET. These data are consistent with the known regiochemical selectivity of CYP2C11 (Qu et al, 1998) Fig. 5.…”
Section: Resultssupporting
confidence: 81%
“…Previous studies have demonstrated that CYP102 F87V and CYP2C11-CYPOR are active arachidonic acid epoxygenases that biosynthesize the EETs (Capdevila et al, 1992a;Graham-Lorence et al, 1997;Qu et al, 1998;Helvig and Capdevila, 2000). Transfection of BAECs with CYP102 F87V-pCB6 or CYP2C11-CYPOR-pCB6 resulted in abundant expression of the corresponding recombinant P450 proteins as determined by immunoblotting with specific P450 antibodies (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although the liver is a well recognized site of P450 aa metabolism [21,42] and P450 aa metabolism was first identified in liver microsomes [43], effects of P450 aa metabolites in liver physiology and pathophysiology have not yet been delineated. Effects of EETs on liver cells or liver microsomes include increased intracellular Ca 2+ , vasopressin stimulated glycogenolysis, activation of phosphorylase and ADP ribosylation (reviewed in Spector and Norris [16]).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, treatment of fish or avian species with aromatic hydrocarbons, such as benzo [a]pyrene or 2,3,7,8-tetrachlorodibenzo-p-dioxin, increases EET biosyn-thesis, probably by inducing liver CYP1A subfamily P450s (Gilday et al, 1998;Schlezinger et al, 1998). In contrast, fasting of rats leads to reduced liver CYP2C11 expression and decreased hepatic arachidonic acid epoxygenase activity (Qu et al, 1998). Much less is known about factors that regulate expression of kidney P450 epoxygenases.…”
mentioning
confidence: 98%
“…Xenochemicals such as ␤-naphthoflavone, phenobarbital, and clofibrate are known to induce liver CYP1A, CYP2B, CYP4A subfamily P450s, respectively (Capdevila et al, 1990;Wu et al, 1997;Gilday et al, 1998;Schlezinger et al, 1998). Other factors, including nutritional status, developmental factors, inflammatory stimuli, nitric oxide, hormonal status, and certain disease states, such as diabetes, are also known to influence hepatic P450 expression and monooxygenase activities (Thummel and Schenkman, 1990;Nelson et al, 1996;Qu et al, 1998;Ma et al, 1999). In particular, a number of studies have documented a role for sex hormones in regulating the expression of liver P450s (Morgan et al, 1985;Waxman et al, 1985;McClellan-Green et al, 1989;Thummel and Schenkman, 1990;.…”
mentioning
confidence: 99%